PLA / PBAT composite material and preparation method thereof

Through the two-step crosslinking method, PBAT is first pre-crosslinked and then crosslinked with PLA to form a PLA-PBAT co-crosslinking layer, which solves the problems of low toughness and strength of existing PLA/PBAT composite materials, and achieves mechanical stability and The tensile strength is improved and suitable for large-scale production.

CN119286212APending Publication Date: 2025-01-10SHENZHEN GEEKVAPE TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411507318.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing preparation methods of PLA/PBAT composites lead to low toughness and strength of the material, poor mechanical stability, and prone to excessive crosslinking to cause the material to become hard and brittle.

Method used

Using the two-step crosslinking method, PBAT is first reacted with the crosslinking agent and the initiator to form pre-crosslinked pellets, and then mixed with PLA for secondary crosslinking. By controlling the extruder temperature and screw speed, excessive crosslinking is avoided. Form a PLA-PBAT co-crosslinked layer to improve the mechanical properties of the material.

Benefits of technology

It significantly improves the tensile strength and stiffness of PLA/PBAT composite materials, has good mechanical stability, avoids the material embrittlement caused by excessive crosslinking, and simplifies the process flow, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286212A_ABST
    Figure CN119286212A_ABST
Patent Text Reader

Abstract

The invention is suitable for a high polymer material technology, and discloses a preparation method of a PLA / PBAT composite material and the PLA / PBAT composite material prepared by the method. The preparation method of the PLA / PBAT composite material comprises the following steps: mixing PBAT, an initiator and a cross-linking agent to obtain a first mixture; the first mixture is subjected to melt extrusion in an extruder, and pre-crosslinked PBAT granules are obtained; pLA and the PBAT granules are mixed, and a second mixture is obtained; the second mixture is subjected to melt extrusion in the extruder, and the PLA / PBAT composite material is obtained. The PLA / PBAT composite material prepared by the preparation method provided by the invention is good in mechanical stability and relatively good in tensile strength and rigidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to polymer material technology, and in particular to a method for preparing a PLA / PBAT composite material and a PLA / PBAT composite material prepared by the method. Background Art

[0002] Polylactic acid (PLA) is a biodegradable biocompatible thermoplastic. Due to its high mechanical properties, thermoplasticity and commercial availability, PLA has been widely used in biomedicine, pharmaceuticals, agriculture and other fields. However, PLA has high brittleness, low glass transition temperature and poor thermal stability, which limits its application. Blending PLA with plasticizers is the most common and effective method to increase polymer toughness. Poly (butylene adipate-co-terephthalate) (PBAT) is a biodegradable aliphatic-aromatic copolyester, which has high toughness and also possesses biodegradability, and is an ideal material for PLA toughening.

[0003] The existing solution is to mix PBAT and PLA together by physical blending to form a PLA / PBAT composite material. Although this method can improve the toughness of PLA, due to the poor compatibility between PBAT and PLA, the addition of PBAT will significantly reduce the tensile strength and stiffness of the composite material.

[0004] Another method is to form a co-crosslinked structure of PBAT and PLA through chemical crosslinking, thereby improving the performance of the composite material. However, the existing chemical crosslinking method still has some problems, resulting in poor mechanical stability of the obtained composite material, and excessive crosslinking of PBAT and PLA, resulting in a more brittle and harder composite material. Summary of the invention

[0005] The present invention mainly solves the technical problems that the PLA / PBAT composite material prepared has low toughness and strength, poor mechanical stability, and is hard and brittle due to certain defects in the preparation method of the existing PLA / PBAT composite material.

[0006] According to the first aspect, an embodiment provides a method for preparing a PLA / PBAT composite material, comprising the following steps:

[0007] Mixing PBAT, an initiator, and a cross-linking agent to obtain a first mixture;

[0008] Melt-extrude the first mixture in an extruder to obtain pre-crosslinked PBAT pellets;

[0009] Mixing PLA and the PBAT pellets to obtain a second mixture;

[0010] The second mixture is melt-extruded in the extruder to obtain a PLA / PBAT composite material.

[0011] It should be noted that the present application cleverly reacts PBAT with a crosslinker and an initiator first, rather than crosslinking PLA, PBAT, a crosslinker and an initiator together. This method can not only reduce the hardening and brittleness of the material caused by excessive crosslinking of PLA and PBAT; moreover, this method has a simple process and is conducive to large-scale and efficient production. The existing technical solution is to mix all the materials together for crosslinking (referred to as the one-step crosslinking method), while the present application is a technical solution that pre-crosslinks PBAT and then crosslinks it with PLA (referred to as the two-step crosslinking method). Relatively speaking, the existing one-step crosslinking method often forms only a small amount of network crosslinked structure due to insufficient crosslinking reaction, resulting in its impact performance being lower than that of the composite material prepared by the two-step crosslinking method of the present application.

[0012] In one embodiment, the extruder has at least two heating zones, and the temperature of each heating zone in the step of melt-extruding the second mixture in the extruder is higher than the temperature of the corresponding heating zone in the step of melt-extruding the first mixture in the extruder.

[0013] In this embodiment, assuming that the extruder has four heating zones, the temperature of zone one when the second mixture is melt-extruded in the extruder is greater than the temperature of zone one when the first mixture is melt-extruded in the extruder, the temperature of zone two when the second mixture is melt-extruded in the extruder is greater than the temperature of zone two when the first mixture is melt-extruded in the extruder, the temperature of zone three when the second mixture is melt-extruded in the extruder is greater than the temperature of zone three when the first mixture is melt-extruded in the extruder, and the temperature of zone four when the second mixture is melt-extruded in the extruder is greater than the temperature of zone four when the first mixture is melt-extruded in the extruder.

[0014] It should be noted that during the first melt extrusion process of the two-step crosslinking method, the temperature of each heating zone of the extruder is set relatively low, which not only prevents the degradation of PBAT, but also keeps the processing temperature of the pre-crosslinking below the temperature at which the initiator decomposes violently, which can effectively slow down the decomposition of the initiator, avoid excessively intense crosslinking reactions between the crosslinking agent and PBAT, and ensure the crosslinking processability of PBAT. During the second melt extrusion process of the two-step crosslinking method, the temperature of each heating zone of the extruder is set relatively high, which can cause the initiator to decompose violently and generate free radicals. In the presence of these free radicals, the crosslinking agent reacts with the CH2 group in the main chain of PBAT, causing micro-crosslinking of PBAT. At the same time, at the interface between PLA and PBAT, the crosslinking agent induces co-crosslinking between PLA and PBAT to form a PLA-PBAT co-crosslinking layer, which is beneficial to improving the mechanical properties of the composite material.

[0015] In one embodiment, the extruder has four heating zones, and the temperature conditions in the step of melt-extruding the first mixture in the extruder are:

[0016] The temperature of zone 1 is 100-140℃, the temperature of zone 2 is 110-150℃, the temperature of zone 3 is 120-160℃, and the temperature of zone 4 is 150-165℃. The temperature range of the four mold zones is controlled between 100-165℃ during the pre-crosslinking process. This temperature setting can effectively slow down the decomposition of the initiator and ensure the crosslinking processability of PBAT.

[0017] It should be noted that the present application creatively divides the pre-crosslinking process into four stages, controls the temperature of each stage separately, and sets the temperature of the entire stage between 100-165°C, wherein 165°C is lower than the temperature at which the initiator decomposes violently. Such a temperature setting can effectively slow down the decomposition of the initiator and ensure the crosslinking processability of PBAT. The entire pre-crosslinking process is carried out at a temperature lower than the temperature at which the initiator decomposes violently, which can avoid an overly intense crosslinking reaction between the crosslinker and PBAT at this stage, and can also avoid excessively high reaction temperatures that cause partial degradation of PBAT, thereby avoiding the material becoming too hard and brittle in the secondary crosslinking stage, resulting in a significant decrease in impact strength.

[0018] In one embodiment, in the step of melt-extruding the first mixture in an extruder, the speed of the screw of the extruder is 100-300 rpm; and / or, in the step of melt-extruding the second mixture in the extruder, the speed of the screw of the extruder is 100-300 rpm.

[0019] It should be noted that, unlike the relatively simple process of general blending process, dynamic crosslinking strongly depends on shear strength and vulcanization temperature. This application changes the shear strength by adjusting the speed of the pre-crosslinking screw, combined with the above-mentioned control of the pre-crosslinking temperature, so that the PBAT is crosslinked synchronously as much as possible, so that it is sheared into a dispersed phase, so that the PLA / PBAT composite material prepared in this application has better mechanical stability and stronger tensile strength and stiffness.

[0020] In one embodiment, the extruder has four heating zones, and the temperature conditions in the step of melt-extruding the second mixture in the extruder are:

[0021] The temperature of zone one is 140-160℃, the temperature of zone two is 150-170℃, the temperature of zone three is 170-185℃, and the temperature of zone four is 175-190℃.

[0022] It should be noted that in the second melt extrusion process of the two-step crosslinking method, by setting the temperature of the extruder at 140°C-190°C, as the reaction temperature increases, the initiator begins to decompose violently and produce free radicals. In the presence of these free radicals, the crosslinker reacts with the CH2 group in the PBAT main chain, causing micro-crosslinking of PBAT. At the same time, at the interface between PLA and PBAT, the crosslinker induces co-crosslinking between PLA and PBAT to form a PLA-PBAT co-crosslinking layer, which is beneficial to improve the mechanical properties of the composite material.

[0023] In one embodiment, the conditions for mixing PBAT, initiator and cross-linking agent are: mixing at room temperature at a speed of 100-300 rpm for 10-20 min;

[0024] The conditions for mixing the PLA and the PBAT pellets are: mixing at room temperature at a rotation speed of 100-300 rpm for 10-20 minutes.

[0025] In one embodiment, before the step of mixing PBAT, initiator and cross-linking agent, the following steps are further included:

[0026] Drying PBAT and PLA;

[0027] Among them, the drying temperature is 100-130°C and the drying time is 4-8h.

[0028] In one embodiment, the PLA, the PBAT, the crosslinking agent, and the initiator are mixed according to the following mass fractions:

[0029] PLA: 50-70 parts;

[0030] PBAT: 30-50 parts;

[0031] Cross-linking agent: 0.1-0.8 parts;

[0032] Initiator: 0.1-0.5 parts.

[0033] It should be noted that in the present application, the amount of crosslinking agent and initiator added is small, the cost is controllable, and it is conducive to large-scale production, meeting the market demand for low-cost, environmentally friendly materials.

[0034] In one embodiment, the decomposition temperature of the initiator is greater than or equal to 100°C and less than or equal to 200°C.

[0035] It should be noted that, since the processing temperature of pre-crosslinking is between 100-165°C, by selecting an initiator with a decomposition temperature greater than or equal to 100°C and less than or equal to 200°C, the processing temperature of pre-crosslinking can be kept below the temperature at which the initiator decomposes violently, thereby effectively slowing down the decomposition of the initiator, avoiding an overly intense crosslinking reaction between the crosslinking agent and PBAT, and ensuring the crosslinking processability of PBAT.

[0036] According to the second aspect, an embodiment provides a PLA / PBAT composite material, which is prepared by the preparation method of the PLA / PBAT composite material of the first aspect.

[0037] According to the preparation method of the PLA / PBAT composite material of the above embodiment and the PLA / PBAT composite material prepared by the preparation method, due to the use of a two-step crosslinking method, that is, secondary crosslinking (the first mixture is pre-crosslinked in the extruder, and the second mixture is crosslinked in the extruder in two steps), the crosslinking reaction is fully carried out, the formation of the three-dimensional structure of the composite material is increased, and its mechanical stability is improved. Compared with the composite material obtained by the physical blending method, the toughness and strength are effectively improved. In addition, by reacting PBAT with a crosslinking agent and an initiator first, rather than pre-crosslinking PLA, PBAT, a crosslinking agent and an initiator together, excessive crosslinking of PLA and PBAT is avoided, thereby preventing the material from becoming hard and brittle due to excessive crosslinking. Therefore, the PLA / PBAT composite material prepared by the preparation method has good mechanical stability, and both tensile strength and stiffness are better. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a scanning electron microscope image of the cross section of the PLA / PBAT composite material prepared in Example 2 after tensile testing. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below by specific embodiments in conjunction with the accompanying drawings. In the following embodiments, many detailed descriptions are intended to enable the present application to be better understood. However, those skilled in the art can effortlessly recognize that some of the features can be omitted in different situations, or can be replaced by other elements, materials, and methods. In some cases, some operations related to the present application are not shown or described in the specification, in order to avoid the core part of the present application being overwhelmed by too much description, and for those skilled in the art, it is not necessary to describe these related operations in detail, and they can fully understand the related operations according to the description in the specification and the general technical knowledge in the art.

[0040] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementations. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the drawings are only for the purpose of clearly describing a certain embodiment and are not meant to be a required sequence, unless otherwise specified that a certain sequence must be followed.

[0041] The serial numbers assigned to the components in this article, such as "first", "second", etc., are only used to distinguish the objects described and do not have any order or technical meaning.

[0042] As used herein, "room temperature" refers to 23°C ± 2°C.

[0043] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0044] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0045] The present invention provides a method for preparing a PLA / PBAT composite material and a PLA / PBAT composite material prepared by the method.

[0046] The preparation method of the PLA / PBAT composite material provided by the present invention uses the following components in parts by mass to prepare the PLA / PBAT composite material:

[0047] Polylactic acid (PLA): 50-70 parts;

[0048] Poly(butylene adipate-co-terephthalate) (PBAT): 30-50 parts;

[0049] Cross-linking agent: 0.1-0.8 parts;

[0050] Initiator: 0.1-0.5 parts;

[0051] Antioxidants: 0.5-2 parts;

[0052] Compatibilizer: 0.5-3 parts.

[0053] Wherein, PLA is one or more of NatureWorks 4032D (hereinafter abbreviated as 4032D), Luminy LX175 (hereinafter abbreviated as LX175), REVODE 101 (hereinafter abbreviated as 101), Fengyuan FY801 (hereinafter abbreviated as FY801), PBAT is one or more of Tunhe TH801T (hereinafter abbreviated as TH801T), Huiyang HY-CM-6 (hereinafter abbreviated as HY-CM-6), Sangosen L00022A (hereinafter abbreviated as L00022A), the crosslinking agent is one or more of diisopropylbenzene peroxide, polyisocyanate, polyhydroxy phosphate, and formaldehyde acetal resin, and the initiator is tert-butyl peroxide TB HP (hereinafter abbreviated as TBHP), polypropylene carbonate, p-toluene diisocyanate, zinc chloride, the antioxidant is one or more of antioxidant 1076 (hereinafter abbreviated as 1076), antioxidant 1010 (hereinafter abbreviated as 1010), antioxidant 412S (hereinafter abbreviated as 412S) and antioxidant 1135 (hereinafter abbreviated as 1135), and the compatibilizer is one or more of 6902, maleic anhydride, epoxy furan resin, ethylene-methyl acrylate-glycidyl methacrylate.

[0054] Antioxidants are used to prevent PLA and PBAT from being oxidized and degraded, and solubilizers are helpful in increasing the compatibility of PLA and PBAT mixed together to avoid degradation of PLA and PBAT, thereby improving the mechanical properties of PLA / PBAT composites.

[0055] The preparation method of the PLA / PBAT composite material provided by the present invention comprises the following steps:

[0056] Step 1), drying: drying PBAT and PLA, wherein the drying temperature is 100-130°C and the drying time is 4-8h;

[0057] Step 2), preparing a first mixture: mixing PBAT, an initiator and a cross-linking agent in a high-speed mixer at a speed of 100-300 rpm at room temperature for 10-20 minutes to obtain a first mixture;

[0058] Step 3), pre-crosslinking: adding the first mixture obtained in step 2) into a twin-screw extruder for melt extrusion to obtain pre-crosslinked PBAT pellets; wherein the twin-screw extruder has four heating zones, the temperature of zone 1 is 100-140°C, the temperature of zone 2 is 110-150°C, the temperature of zone 3 is 120-160°C, and the temperature of zone 4 is 150-165°C; the screw speed is 100-300rpm;

[0059] Step 4), preparation of a second mixture: PLA, an antioxidant, a compatibilizer and the PBAT pellets obtained in step 3) are mixed in a high-speed mixer at a speed of 100-300 rpm at room temperature for 10-20 minutes to obtain a second mixture;

[0060] Step 5), two-step cross-linking: melt-extrude the second mixture in the twin-screw extruder used in step 3) to obtain a PLA / PBAT composite material; wherein the temperatures of the four heating zones of the twin-screw extruder are: the temperature of zone 1 is 140-160°C, the temperature of zone 2 is 150-170°C, the temperature of zone 3 is 170-185°C, and the temperature of zone 4 is 175-190°C; the screw speed is 100-300rpm.

[0061] The preparation method of the PLA / PBAT composite material provided by the present invention adopts a secondary extrusion and dynamic cross-linking method to prepare the PLA / PBAT composite material. By improving the interface bonding strength of the composite material and improving its micro-cross-linked elastomer, the prepared PLA / PBAT composite material achieves excellent notched impact strength and tensile strength, and its tensile strength and stiffness are both good, which is a PLA / PBAT composite material with both toughness and strength.

[0062] Example 1 to Example 7

[0063] The raw materials were weighed according to the component parameters in Table 1, and the PLA / PBAT composite materials were prepared according to the above preparation method and the process parameters in Table 1 to obtain the PLA / PBAT composite materials of different embodiments.

[0064] Table 1

[0065]

[0066] In addition, in each embodiment, PBAT and PLA were dried at 120°C for 6 hours before subsequent operations. When preparing the first mixture, PBAT, initiator and crosslinker were mixed in a high-speed mixer at a speed of 200 rpm at room temperature for 15 minutes to obtain the first mixture; when preparing the second mixture, PLA, antioxidant, compatibilizer and PBAT pellets were mixed in a high-speed mixer at a speed of 200 rpm at room temperature for 15 minutes to obtain the second mixture.

[0067] Comparative Example 1

[0068] Compared with Example 2, this comparative example did not add a crosslinking agent and an initiator, that is, no crosslinking reaction was performed, and a melt extrusion operation was performed. The temperatures of the four heating zones for melt extrusion in the twin-screw extruder were: the temperature of the first zone was 150° C., the temperature of the second zone was 160° C., the temperature of the third zone was 175° C., and the temperature of the fourth zone was 180° C. (the temperature setting was the same as the temperature setting in the two-step crosslinking step of Example 2).

[0069] Comparative Example 2

[0070] Compared with Example 2, the screw speed of the twin-screw extruder in this comparative example is lower during pre-crosslinking, that is, shearing is performed by low shear intensity. The screw speed is 50 rpm.

[0071] Comparative Example 3

[0072] Compared with Example 2, in this comparative example, the temperature of the four heating zones of the twin screw extruder during pre-crosslinking is set higher. The temperatures of the four heating zones of the twin screw extruder during pre-crosslinking are: the temperature of zone 1 is 160°C, the temperature of zone 2 is 170°C, the temperature of zone 3 is 180°C, and the temperature of zone 4 is 190°C.

[0073] Comparative Example 4

[0074] Compared with Example 2, in this comparative example, PLA, PBAT, a crosslinking agent, an initiator, an antioxidant and a compatibilizer are mixed and a melt extrusion operation is performed, that is, a crosslinking reaction is performed. Among them, the temperatures of the four heating zones for melt extrusion in the twin-screw extruder are: the temperature of the first zone is 150°C, the temperature of the second zone is 160°C, the temperature of the third zone is 175°C, and the temperature of the fourth zone is 180°C (this temperature setting is the same as the temperature setting in the two-step crosslinking step of Example 2).

[0075] Comparative Example 5

[0076] Compared with Example 2, the mass fraction of the crosslinking agent added in this comparative example is higher. Among them, 1 g of the crosslinking agent is added.

[0077] Result analysis:

[0078] The PLA / PBAT composite materials obtained in Examples 1-7 and Comparative Examples 1-5 were tested for tensile properties (tensile strength and elongation at break) and impact strength (notched impact strength) of thermoplastic bioplastics. The tensile properties of thermoplastic bioplastics were tested in accordance with GB / T13022-1991 Plastic Film Tensile Properties Test Method, and the impact strength of thermoplastic bioplastics was tested in accordance with IS0179-1:2000. The PLA / PBAT composite materials were dried at 100°C for 12 hours before testing, and the test environment was 23±1°C and 50±5% rh. The test results are shown in Table 2.

[0079] Table 2

[0080] Tensile strength(MPa) <![CDATA[Notched impact strength (kJ / m 2 )]]> Elongation at break (%) Example 1 39.6 21.9 122.4 Example 2 43.1 40.2 156.9 Example 3 43.5 25.6 89.1 Example 4 44.7 22.4 76.2 Example 5 44.4 20.7 62.3 Example 6 40.1 38.3 153.3 Example 7 45.2 41.2 162.9 Comparative Example 1 26.3 11.1 9.8 Comparative Example 2 28.9 22.4 60.8 Comparative Example 3 44.2 12.7 25.4 Comparative Example 4 35.5 18.3 98.2 Comparative Example 5 45.3 23.1 10.5

[0081] Compared with Example 1 and Comparative Example 1, the addition of the crosslinking agent effectively enhances the toughness of the PLA / PBAT composite material. 0.1g of the crosslinking agent can increase the notched impact strength of the PLA / PBAT composite material from 11.1kJ / m to 1.5kJ / m. 2 Increased to 21.9 kJ / m 2 , increased by 97.3%; its elongation at break increased from 9.8% to 122.4%, an increase of 1148.98%. Comparing Example 2 and Comparative Example 1, 0.4g of crosslinking agent can increase the notched impact strength of the PLA / PBAT composite material from 11.1kJ / m 2 Increased to 40.2 kJ / m 2 , increased by 262.16%; its elongation at break increased from 9.8% to 156.9%, an increase of 1501.02%. This fully demonstrates that the crosslinking agent effectively enhances the toughness of PBAT.

[0082] Comparative Examples 1 to 3, as the amount of crosslinking agent added increases, the notched impact properties are effectively enhanced, especially when the amount of crosslinking agent increases from 0.1 g to 0.4 g, the improvement is obvious, from 21.9 kJ / m 2 Increased to 40.2 kJ / m 2 , increased by 83.6%. This is because when the PLA / PBAT composite material is impacted by external force, the network structure achieved by the cross-linking reaction of PBAT and PLA has a stronger energy absorption capacity than the linear structure obtained by simply blending PBAT and PLA. In addition, the co-cross-linking of PLA and PBAT at the interface enhances the interfacial compatibility of the PLA / PBAT composite material. When the PLA / PBAT composite material is impacted, the PLA and PBAT can effectively transfer energy to each other.

[0083] Figure 1The cross-sectional electron microscope scanning image after tensile testing of the PLA / PBAT composite material prepared in Example 2 is shown. As can be seen from the figure, after the tensile test, the fracture of the sample is relatively rough and the tearing phenomenon is obvious, which can indicate that the PLA / PBAT composite material prepared in Example 2 has a strong interface interaction, and its mechanical test results are also consistent with its excellent tensile strength, notched impact strength and elongation at break.

[0084] Comparing Example 2 and Example 3, it can be found that when the cross-linking agent is increased from 0.4g to 0.8g, the notched impact performance of the PLA / PBAT composite material is not greatly improved, and the notched impact strength and elongation at break are greatly reduced. This phenomenon indicates that it may be due to excessive cross-linking of PBAT and PLA, and the PBAT / PLA composite material prepared by excessive cross-linking loses elasticity, resulting in a decrease in its impact strength. On the other hand, in Comparative Example 2 and Comparative Example 5, too much cross-linking agent greatly increases the melt viscosity, making it difficult to disperse PBAT in PLA.

[0085] Through the above analysis, the best addition amount of the crosslinking agent is 0.1-0.8 by weight. If the addition amount is too low, it is not conducive to increasing the toughness of PBAT. If the addition amount is too high, the melt viscosity will be greatly increased, resulting in difficulty in dispersing PBAT in PLA.

[0086] Please refer to the examples and comparative example 3. In examples 1 to 7, the temperatures of the four heating zones of the twin-screw extruder in the pre-crosslinking stage are respectively set to: the temperature of zone 1 is 100-140°C, the temperature of zone 2 is 110-150°C, the temperature of zone 3 is 120-160°C, and the temperature of zone 4 is 150-165°C; the tensile strength of the obtained PLA / PBAT composite material is between 39.6-45.2MPa, and the notched impact strength is between 20.7-41.2kJ / m 2 The elongation at break is between 62.3-162.9%, and the tensile strength, notched impact strength and elongation at break are all excellent. In Comparative Example 3, the temperatures of the four heating zones of the twin-screw extruder during pre-crosslinking are set to: the temperature of zone 1 is 160°C, the temperature of zone 2 is 170°C, the temperature of zone 3 is 180°C, and the temperature of zone 4 is 190°C; the tensile strength of the obtained PLA / PBAT composite material is 44.2MPa, the notched impact strength is 12.7kJ / m2, and the elongation at break is 25.4%, and the notched impact strength and elongation at break are greatly reduced.

[0087] It can be seen that when the temperature of melt extrusion in the pre-crosslinking stage is too high, it causes the initiator to decompose violently, which can prematurely promote the crosslinking of PBAT and lead to a decrease in its mechanical properties. In addition, since the temperature of melt extrusion during the two-step crosslinking is higher than the temperature of melt extrusion in the pre-crosslinking stage, when the temperature of melt extrusion in the pre-crosslinking stage is set too high, PBAT needs to undergo two high-temperature melt extrusions, and a small amount of PBAT degradation may occur, further weakening its mechanical properties. Therefore, in the pre-crosslinking stage, the temperature of the first zone of the twin-screw extruder is set to 100-140°C, the temperature of the second zone is set to 110-150°C, the temperature of the third zone is set to 120-160°C, and the temperature of the fourth zone is set to 150-165°C, so that a PLA / PBAT composite material with excellent tensile strength, notched impact strength and elongation at break can be obtained.

[0088] It should be noted that in the two-step cross-linking method of the present application, the temperature of the extruder in the first melt extrusion process is set lower than that in the second melt extrusion process, so that the processing temperature in the pre-cross-linking stage can be kept below the temperature at which the initiator decomposes violently, avoiding an overly intense cross-linking reaction between the cross-linking agent and PBAT, and avoiding partial degradation of PBAT due to excessively high reaction temperature, which can guarantee the cross-linking processability of PBAT to a greater extent. In the second melt extrusion process, as the reaction temperature increases, the initiator begins to decompose violently and produces free radicals; in the presence of these free radicals, the cross-linking agent reacts with the CH2 group in the PBAT main chain, causing micro-cross-linking of PBAT. At the same time, at the interface between PLA and PBAT, the cross-linking agent induces co-cross-linking between PLA and PBAT to form a PLA-PBAT co-cross-linking layer, which is beneficial to improving the mechanical properties of the blend.

[0089] Please refer to Example 2, Example 6, Example 7 and Comparative Example 2. In Example 2, Example 6 and Example 7, the screw speed of the twin-screw extruder during pre-crosslinking is set between 100-300 rpm, and the tensile strength of the obtained PLA / PBAT composite material is between 40.1-45.2 MPa, and the notched impact strength is between 38.3-41.2 kJ / m 2 The tensile strength, notched impact strength and elongation at break are all excellent. In Comparative Example 2, the screw speed of the twin-screw extruder during pre-crosslinking is set to 50 rpm, and the tensile strength of the obtained PLA / PBAT composite material is 28.9 MPa, the notched impact strength is 22.4 kJ / m2, and the elongation at break is 60.8%. It can be seen that setting the screw speed of the twin-screw extruder between 100-300 rpm during pre-crosslinking can improve the mechanical properties of the PLA / PBAT composite material without affecting the toughness of the composite material too much. This method is low-cost and more environmentally friendly.

[0090] It should be noted that, unlike the relatively simple process of general blending process, dynamic crosslinking strongly depends on shear strength and vulcanization temperature. This application changes the shear strength by adjusting the speed of the pre-crosslinking screw, and combines the control of the pre-crosslinking temperature to make PBAT crosslinked synchronously as much as possible, so that it is sheared into a dispersed phase, so that the PLA / PBAT composite material prepared in this application has better mechanical stability and stronger tensile strength and stiffness.

[0091] Please refer to Example 2 and Comparative Examples 1 and 4, wherein Example 2 adopts the two-step crosslinking method of the present invention, and the tensile strength of the obtained PLA / PBAT composite material is 43.1 MPa, the notched impact strength is 40.2 kJ / m2, and the elongation at break is 156.9%; Comparative Example 1 does not perform a crosslinking reaction, and the tensile strength of the obtained PLA / PBAT composite material is 26.3 MPa, the notched impact strength is 11.1 kJ / m2, and the elongation at break is 9.8%; Comparative Example 4 adopts a one-step crosslinking method, and the tensile strength of the obtained PLA / PBAT composite material is 35.5 MPa, the notched impact strength is 18.3 kJ / m2, and the elongation at break is 98.2%. It can be found that although the one-step crosslinking method (Comparative Example 4) has better mechanical properties than the PBAT / PLA composite material prepared without crosslinking reaction (Comparative Example 1), the PBAT / PLA composite material prepared by the one-step crosslinking method is lower in tensile strength, notched impact strength and elongation at break than the PBAT / PLA composite material prepared by the two-step crosslinking method (Example 2), and the notched impact strength and elongation at break are reduced by a greater margin, which indicates that the crosslinking reaction of the one-step crosslinking method is insufficient, the three-dimensional structure formed is small, and the mechanical stability is poor. Therefore, the two-step crosslinking method is adopted to increase the formation of the three-dimensional structure of the composite material through a more sufficient crosslinking reaction, thereby greatly improving the mechanical stability of the PBAT / PLA composite material.

[0092] The preparation method of the PLA / PBAT composite material provided by the present invention has the following beneficial effects:

[0093] 1) The one-step cross-linking method often forms a small amount of network cross-linked structure in the composite material due to insufficient cross-linking reaction, which will lead to its low impact performance. By adopting the two-step cross-linking method (i.e., secondary cross-linking: pre-cross-linking and two-step cross-linking), the cross-linking reaction is fully carried out, the formation of the three-dimensional structure of the composite material is increased, and its mechanical stability is improved. Specifically, during the second melt extrusion process of the two-step cross-linking method, as the reaction temperature increases, the initiator begins to decompose violently and produce free radicals. In the presence of these free radicals, the cross-linking agent reacts with the CH2 group in the PBAT main chain, causing micro-cross-linking of PBAT. At the same time, at the interface between PLA and PBAT, the cross-linking agent induces co-cross-linking between PLA and PBAT to form a PLA-PBAT co-cross-linking layer, which is beneficial to improve the mechanical properties of the composite material.

[0094] 2) The present invention allows PBAT to react with a crosslinking agent and an initiator first, rather than pre-crosslinking PLA, PBAT, a crosslinking agent and an initiator together, thereby reducing the hardening and brittleness of the material caused by excessive crosslinking of PLA and PBAT. At the same time, this method has a simple process, a low amount of crosslinking agent and initiator added, and a controllable cost, which is conducive to large-scale production and can meet the market demand for high-efficiency, low-cost, and environmentally friendly materials.

[0095] 3) The temperature of the four-stage heating zone of the twin-screw extruder in the pre-crosslinking stage is set to be lower than the temperature of the corresponding heating zone of the twin-screw extruder in the second-step crosslinking stage, so that the temperature in the pre-crosslinking stage is kept below the temperature at which the initiator decomposes violently, which can avoid an overly intense crosslinking reaction between the crosslinking agent and PBAT, and can also avoid excessive reaction temperature causing partial degradation of PBAT, thereby avoiding the material becoming too hard and brittle in the secondary crosslinking stage, resulting in a significant decrease in impact strength. Among them, in the pre-crosslinking stage, the temperature of the four-stage heating zone of the twin-screw extruder is controlled between 100-165°C. Such a temperature setting can effectively slow down the decomposition of the initiator and ensure the crosslinking processability of PBAT.

[0096] 4) The present invention changes the shear strength by adjusting the screw speed in the pre-crosslinking stage, and combines the control of the temperature in the pre-crosslinking stage to allow the PBAT to be synchronously crosslinked as much as possible, so that it is sheared into a dispersed phase.

[0097] The above specific examples are used to illustrate the present invention, which is only used to help understand the present invention and is not intended to limit the present invention. For those skilled in the art, according to the concept of the present invention, some simple deductions, modifications or substitutions can be made.

Claims

1. A method for preparing a PLA / PBAT composite material, characterized in that: The following steps are involved: Mixing PBAT, an initiator, and a cross-linking agent to obtain a first mixture; Melt-extrude the first mixture in an extruder to obtain pre-crosslinked PBAT pellets; Mixing PLA and the PBAT pellets to obtain a second mixture; The second mixture is melt-extruded in the extruder to obtain a PLA / PBAT composite material.

2. The method for preparing the PLA / PBAT composite material according to claim 1, characterized in that: The extruder has at least two heating zones, and the temperature of each heating zone in the step of melt-extruding the second mixture in the extruder is higher than the temperature of the corresponding heating zone in the step of melt-extruding the first mixture in the extruder.

3. The method for preparing the PLA / PBAT composite material according to claim 2, characterized in that: The extruder has four heating zones, and the temperature conditions in the step of melt-extruding the first mixture in the extruder are: The temperature of zone 1 is 100-140℃, the temperature of zone 2 is 110-150℃, the temperature of zone 3 is 120-160℃, and the temperature of zone 4 is 150-165℃.

4. The method for preparing the PLA / PBAT composite material according to claim 3, characterized in that: In the step of melt-extruding the first mixture in an extruder, the speed of the screw of the extruder is 100-300 rpm; and / or, in the step of melt-extruding the second mixture in the extruder, the speed of the screw of the extruder is 100-300 rpm.

5. The method for preparing the PLA / PBAT composite material according to any one of claims 2 to 4, characterized in that: The extruder has four heating zones, and the temperature conditions in the step of melt-extruding the second mixture in the extruder are: The temperature of zone one is 140-160℃, the temperature of zone two is 150-170℃, the temperature of zone three is 170-185℃, and the temperature of zone four is 175-190℃.

6. The method for preparing the PLA / PBAT composite material according to claim 1, characterized in that: The conditions for mixing the PBAT, initiator and cross-linking agent are: mixing at room temperature at a speed of 100-300 rpm for 10-20 minutes; The conditions for mixing the PLA and the PBAT pellets are: mixing at room temperature at a rotation speed of 100-300 rpm for 10-20 minutes.

7. The method for preparing the PLA / PBAT composite material according to claim 1, characterized in that: Before the step of mixing PBAT, initiator and cross-linking agent, the step of: Drying PBAT and PLA; Among them, the drying temperature is 100-130°C and the drying time is 4-8h.

8. The method for preparing the PLA / PBAT composite material according to claim 1, characterized in that: The PLA, the PBAT, the cross-linking agent, and the initiator are mixed according to the following mass parts: PLA: 50-70 parts; PBAT: 30-50 parts; Cross-linking agent: 0.1-0.8 parts; Initiator: 0.1-0.5 parts.

9. The method for preparing the PLA / PBAT composite material according to claim 1, characterized in that: The decomposition temperature of the initiator is greater than or equal to 100°C and less than or equal to 200°C.

10. A PLA / PBAT composite material, characterized in that: The PLA / PBAT composite material is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Cited By

  • Environment-friendly lawn filling particles and preparation method thereof

    CN119842193A

  • An environmentally friendly lawn infill granule and its preparation method

    CN119842193B

  • Self-enhanced PBAT and preparation method of film thereof

    CN119875329A